Characterization of bolting behaviour in garlic (Allium sativum) using SNP - KAUR, YADWINDER; DHALL, R K; SHARMA, PRITI (The Indian Journal of Agricultural Sciences, 2020)
The present research was conducted to evaluate the bolting (incomplete bolters and non-bolters) behaviour in garlic (Allium sativum L.) accessions collected from different geographical areas. A total of 96 genotypes collected from different sources were used for genotype sequencing to identify SNP but only 73 genotypes among them showed good amplification. A primer (AsLFY) was designed by using reference of already designed gene specific primer (gALFY-2) by Rotem et al. (2007). After amplification, sequencing of these 73 genotypes was done; SNP (CCGTCG) was at 301 bp from initiation codon, i.e. G for non-bolters genotypes and A for incomplete bolter genotypes. Thus, the identified SNP would help in detecting incomplete bolter and non-bolter genotypes at seedling stage which can be useful for garlic breeding programmes.